Screening for osteoporosis among post-menopausal women in community pharmacy - Barris Blundell D; Rodriguez Zarzuelo C; Sabio Sanchez B; Gutierrez Alvarez JL; Navarro Visa E; Muñoz Valdes O; Garrido Jimenez B; Sanchez Gomez R (Centro de Investigaciones y Publicaciones Farmaceuticas, 2006)
Objectives: To identify postmenopausal women with risk of osteoporosis through quantitative ultrasound imaging (QUI) and to value the medical intervention after the determination of the bone mineral density (BMD). Methods: Cross-sectional descriptive study developed in a community pharmacy. During the month of June of 2005 the community pharmacy enrolled postmenopausal women into the study. Women in treatment with calcium, vitamin D, hormone replacement therapy, estrogen receptor modulators, calcitonin or biphosphonates were considered criteria for exclusion. To all the women that consent to participate, the pharmacist measured BMD with the device Sahara Hologic Ultrasound Bone Densitometer at right calcaneus. Following the World Health Organization, women were classified as osteoporotic if their T-Score was less than -2.5 and as osteopenic if their T-Score ranged between -2.5 and -1.0. Results: Of the 100 women screened, 11 (11%) presented risk of osteoporosis and 61 (61%) of osteopenia. The 18.5% postmenopausal women with body mass index lesser than 30 presented risk of osteoporosis and the 63.0% osteopenia. Conclusions: The QUI constitutes a useful tool in community pharmacy for the screening of osteoporosis and it supposes a greater integration of the community pharmacy within the health care.